2009
DOI: 10.1080/01621420802716206
|View full text |Cite
|
Sign up to set email alerts
|

Validity Testing the Outcomes and Assessment Information Set (OASIS)

Abstract: This study evaluated the criterion validity of the Outcome and Assessment Instrument Set (OASIS) items that measure activities of daily living (ADLs), instrumental activities of daily living (IADLs), cognitive functioning, and depression. A convenience sample of patients (n = 203) from five home care agencies participated in the study. Patient OASIS items were compared to data collected using gold standard instruments. Correlations range from .44 to .69 for ADLs and .20 to .68 for IADLs. A correlation of .62 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 15 publications
0
57
0
Order By: Relevance
“…Future studies are needed to demonstrate the benefits of providing home health care with bigger sample sizes, a comparison group, and more comprehensive measures on QOL. Although ADL and IADL items in OASIS have been widely used at the home healthcare agencies in the United States, little evidence for the validity and relatively low criterion-related validity reported in a previous study (Tullai-McGuinness & Madigan, 2009) might limit the interpretation of the results in this study. Because the endpoint of measurement was defined in two ways (at discharge or 60 days), the time difference from start of care may not be the same for each subject.…”
Section: Limitationsmentioning
confidence: 86%
See 1 more Smart Citation
“…Future studies are needed to demonstrate the benefits of providing home health care with bigger sample sizes, a comparison group, and more comprehensive measures on QOL. Although ADL and IADL items in OASIS have been widely used at the home healthcare agencies in the United States, little evidence for the validity and relatively low criterion-related validity reported in a previous study (Tullai-McGuinness & Madigan, 2009) might limit the interpretation of the results in this study. Because the endpoint of measurement was defined in two ways (at discharge or 60 days), the time difference from start of care may not be the same for each subject.…”
Section: Limitationsmentioning
confidence: 86%
“…Only one study that reported the criterion-related validity of the scales was found, showing a correlation of .44e.69 in the ADL and .20e.68 in the IADL (Tullai-McGuinness, Madigan, & Fortinsky, 2009). …”
Section: Clinical Outcomesmentioning
confidence: 97%
“…Five of the studies evaluated some form of criterion related validity, the degree to which a measure relates or correlates to some external criterion (Kazdin, 2002; Rubin & Babbie, 2001). Four of these five studies evaluated convergent validity (Trochim, 2006; Weiner et al, 2008), using either a gold standard tool like the Center of Epidemiology Studies Depression Scale (Tullai-McGuinness et al, 2009), Structured Clinical Interview Axis I DSM-IV Disorders (Brown et al, 2004), the certified care plan (Kinatukara et al, 2005), or expert-derived “correct” answers (Madigan et al, 2003) as comparison criteria. Bowles and Cater (2003) evaluated the predictive validity of the case mix weight, the clinical, service, and functional domain scores with regard to risk of hospital readmission.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
“…Items loaded onto one factor with loadings .61 (56.3% of the variance explained) for the items collected at admission and .74 (68.9% of the variance explained) at discharge. Tullai-McGuinness, Madigan, and Fortinsky (2009) tested convergent validity of OASIS items, finding robust correlation between OASIS ADLs and Older Americans Resources and Services (OARS) ADL items (r 5 .71) but only moderate correlations (r 5 .49) between OASIS and OARS ADL measures. OASIS cognitive items and the Short Portable Mental Status Questionnaire showed high to moderate correlation (r 5 .62).…”
Section: Convergent Validity Measuresmentioning
confidence: 98%